Diagnosis And Clinical Course of Chronic Generalised Periodontitis in Connective Tissue Dysplasia - Sunnatullo Gafforov; Ulugbek Nazarov; Gulomjan Khalimbetov (Genius Journals, 2022)
The present study focuses on 104 patients with differentiated connective tissue dysplasia (DCTD) (Marfan syndrome) and undifferentiated connective tissue dysplasia (UDCTD). General clinical investigations - questioning, physical examination, instrumental, biochemical, and chemoluminescent procedures were used.
Keywords: Connective Tissue Dysplasia; Chronic Generalized Periodontitis; Mineral Disorders; Marfan Syndrome